Réponses

Meilleure réponse !
2014-10-14T12:24:09+02:00
F(x)=4x²-3
f(-4)= 4*(-4)²-3 =4*16-3 = 64-3 = 61
f(-2)= 4*(-2)²-3 = 4*4-3 = 16-3 = 13
f(-1)= 4*(-1)²-3 = 4*1-3 = 1
f(0)= 4*0²-3 = -3
f(3)= 4*3²-3 = 4*9-3 = 36-3 = 33
f(4)= 4*4²-3 = 4*16-3 = 64-3 = 61
f(5)= 4*5²-3 = 4*25-3 = 100-3 = 97
f(8)= 4*8²-3 = 4*64-3 = 253
f(9)= 4*9²-3 = 4*81-3 = 321
f(10)= 4*10²-3 = 4*100-3 = 397
image de 5 : 2*5+1 = 10+1 = 11
antécédent de 8 : 8=2x+1 => 7=2x => x=3,5
antécédent de 3 : 3 = 2x+1 => 2=2x => x=1
antécédent de 4 : 4=2x+1 => 3=2x => x=1,5
Merci beaucoup